The implementation of the Picture and Picture Model (PPM) in learning English for High School students - Insi Nabila, Nur; Septian Islamidina, Dinar; Ahsana El-Sulukiyyah, Ana; Adeleke Adeoye, Moses (Indonesian Journal of Multidisciplinary Educational Research, 2025)
This study evaluates the implementation of the Picture and Picture model in teaching procedure texts in class XI at MA Ibnu Sina. This model uses pictures to help students understand the sequence of steps in procedure texts. The research used qualitative thematic analysis with observation and documentation. The results showed that the model effectively improved students' understanding, although challenges related to unfamiliar vocabulary arose. The steps of implementation and challenges, as well as solutions, were described in this research. In the second meeting, a special glossary helped students overcome these difficulties. In conclusion, the Picture and Picture model can enhance student engagement, critical thinking skills, and teamwork in learning procedure texts.